#CondomEmoji: Are urban Indonesians receptive to a social media-based campaign for safer sex?. Issue 5 (6th August 2018) - Ridlo, Ilham Akhsanu; Zein, Rizqy Amelia
Abstract : Purpose: The purpose of this paper is to explore participants' attitudes and receptivity to a #CondomEmoji campaign insofar as investigating whether attitudes and receptivity were important predictors for brand impression and intention to buy. Design/methodology/approach: This study involved 206 research participants who live in Jakarta and Surabaya and who answered online questionnaires to measure attitudes, receptivity to #CondomEmoji advertising, brand impression and intention to buy condoms. Questionnaires were circulated on several social media platforms and instant messaging apps. The participants were asked to watch the #CondomEmoji advertising video before proceeding to fill out the questionnaires. Findings: Research findings suggested that participants mostly held negative attitudes and receptivity to the campaign. Non-sexually active participants were more likely to perceive the advertising as offensive. Attitudes and receptivity were good predictors for brand impression, yet attitude was not significantly attributed to intention to buy condoms. The result was stronger in sexually active participants. Research limitations/implications: Non-sexually active young people need to be more informed about healthy sexual behavior so that they would not feel embarrassed to discuss and ask about sexual behavior. A socially acceptable condom-use advertising campaign needs to be conducted to lessen the resistance of conservative audiences. Originality/value: This paper offers an insight into how conservative audiences may respond to social-media-based campaign of safer sex.